2018
DOI: 10.7567/1882-0786/aaf5c6
|View full text |Cite
|
Sign up to set email alerts
|

High hole mobility (≥500 cm2 V−1 s−1) polycrystalline Ge films on GeO2-coated glass and plastic substrates

Abstract: The highest recorded hole mobility in semiconductor films on insulators has been updated significantly. We investigate the solid-phase crystallization of a densified amorphous Ge layer formed on GeO2-coated insulating substrates. The resulting polycrystalline Ge layer with a glass substrate consists of large grains (~10 μm) and exhibits a hole mobility as high as 620 cm2 V−1 s−1, despite a low process temperature (500 °C). Even for the Ge layer formed on a flexible polyimide substrate at 375 °C, the hole mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
(71 reference statements)
1
27
0
Order By: Relevance
“…29 We recently found that the atomic density of amorphous Ge (a-Ge) significantly influenced subsequent SPC. [30][31][32] By using a densified a-Ge on a GeO 2 underlayer, we fabricated a poly-Ge layer with a hole mobility of 620 cm 2 /V s, 33 which greatly exceeds that of bulk-Si (430 cm 2 /V s). These achievements initiated the prospect of the development of inversion-type poly-Ge n-MOSFETs that surpass Si-MOSFETs.…”
mentioning
confidence: 99%
“…29 We recently found that the atomic density of amorphous Ge (a-Ge) significantly influenced subsequent SPC. [30][31][32] By using a densified a-Ge on a GeO 2 underlayer, we fabricated a poly-Ge layer with a hole mobility of 620 cm 2 /V s, 33 which greatly exceeds that of bulk-Si (430 cm 2 /V s). These achievements initiated the prospect of the development of inversion-type poly-Ge n-MOSFETs that surpass Si-MOSFETs.…”
mentioning
confidence: 99%
“…42 We further updated the Hall hole mobility to 620 cm 2 /V s by thickening Ge, postannealing at 500 °C, and inserting a GeO 2 underlayer. 43,44 This hole mobility is the highest ever recorded for a semiconductor film directly grown on an insulator at temperatures below 900 °C.…”
Section: Introductionmentioning
confidence: 84%
“…29 Additionally, l Hall was updated to 620 cm 2 /Vs by thickening a-Ge, postannealing at 500 C, and inserting GeO 2 underlayer. 30,31 This l Hall is the highest ever recorded for a thin film directly grown on an insulator at temperatures below 900 C. In the present study, we fabricate poly-Ge TFTs using SPC-Ge and discuss the relationship between the film properties (thickness, l Hall , and p) and TFT characteristics (field-effect mobility: l FE and on/off currents). We demonstrate the highest l FE among low-temperature (<500 C) poly-Ge TFTs without minimizing the channel region.…”
mentioning
confidence: 92%